PENGUKURAN TINGKAT KEGUNAAN PADA APLIKASI MONITORING PEMASANGAN JARINGAN PT XYZ DENGAN METODE SYSTEM USABILITY SCALE (SUS): SYSTEM USABILITY SCALE - Kukuh Puji Lestari, Kukuh Puji Lestari; Asrowardi, Imam; Kurniawan, Henry (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2023)
The Network Installation Monitoring Application currently used by PT XYZ in reporting network installation work has never been evaluated for the usability of the application. The measurement of the usability level of the network installation monitoring application is the initial stage to assess the success of website implementation. The research was conducted by giving questionnaires to respondents in the assessment and calculation of the number of sus scores that can be done with a small number of samples. There are 10 questions on the questionnaire with a rating scale of 1 to 5 for a rating of strongly agree. The result of the score calculation shows the number 75.7, so it is included in the good category or the application is feasible to use.